Familial atrial fibrillation mutation M1875T-SCN5A increases early sodium current and dampens the effect of flecainide. Issue 3 (12th December 2022) - O'Reilly, Molly; Sommerfeld, Laura C; O'Shea, C; Broadway-Stringer, S; Andaleeb, S; Reyat, J S; Kabir, S N; Stastny, D; Malinova, A; Delbue, D; Fortmueller, L; Gehmlich, K; et al.
Abstract: Aims: Atrial fibrillation (AF) is the most common cardiac arrhythmia. Pathogenic variants in genes encoding ion channels are associated with familial AF. The point mutation M1875T in the SCN5A gene, which encodes the α-subunit of the cardiac sodium channel Nav 1.5, has been associated with increased atrial excitability and familial AF in patients. Methods and results: We designed a new murine model carrying the Scn5a -M1875T mutation enabling us to study the effects of the Nav 1.5 mutation in detail in vivo and in vitro using patch clamp and microelectrode recording of atrial cardiomyocytes, optical mapping, electrocardiogram, echocardiography, gravimetry, histology, and biochemistry. Atrial cardiomyocytes from newly generated adult Scn5a -M1875T +/− mice showed a selective increase in the early (peak) cardiac sodium current, larger action potential amplitude, and a faster peak upstroke velocity. Conduction slowing caused by the sodium channel blocker flecainide was less pronounced in Scn5a -M1875T +/− compared to wildtype atria. Overt hypertrophy or heart failure in Scn5a -M1875T +/− mice could be excluded. Conclusion: The Scn5a -M1875T point mutation causes gain-of-function of the cardiac sodium channel. Our results suggest increased atrial peak sodium current as a potential trigger for increased atrial excitability. Graphical Abstract: Graphical Abstract